Brhadaranyaka-Upanisad: Text History of the Third Adhyaya - Ježić, Mislav (2014)
On the basis of the previous work of Deussen, Brereton and others, the article analyses the third adhyaya of the Brhadaranyaka-Upanisad and the philosphical tournament between Yajnavalkya and eight contestants described in that chapter. On the basis of textual variants in different Vedic schools it is possible to trace the text history of the chapter. The elaborated scene developed from the contest between Yajnavalkya and the last disputant, Sakalya, through a stage when Uddalaka Aruni and a learned women Gargi Vacaknavi, who comes forward twice, were introduced, until four other contestants were included, and, finally, the fifth one, who disturbed the symmetry of composition of the scene. The results are interesting from the point of view of text history as well as history of ideas.
Projekt MZOS
ENG